Coping Ability and Promotion Countermeasures of Medical and Health Institutions Reputation Crisis: A Case Study in Hubei Province - Liu, Yang; Li, Xiaofang; Ding, Rui; He, Tianrun; Wang, Xian-jia (Frontiers in Public Health, 2022)
At present, the doctor-patient relations in Chinese hospitals are increasingly tense, and the reputation crisis challenges facing hospitals are also more frequent. However, the reputation crisis management level of the hospital is directly related to the future development and construction of the hospital, and is an important management link that cannot be ignored. Therefore, how to quantify the impact of the relevant crisis on hospitals has become a major problem. First of all, this paper uses the situational crisis communication theory to combine the characteristics of hospital reputation crisis with the theory, and classifies hospital reputation crisis from three perspectives: victim crisis, accidental crisis and preventable crisis.Secondly, a more comprehensive analysis of hospital reputation crisis management model is given in the research cases, based on the relevant data of Union Hospital, Tongji Medical College Huazhong University of Science and Technology (UH), Tongji Hospital, Tongji Medical College Huazhong University of Science and Technology (TJ), Zhongnan Hospital of Wuhan University (ZN), Renmin Hospital of Wuhan University (RM), and Maternal and Child Hospital of Hubei Province (MC). Thirdly, we divides the hospital reputation positioning into four types: robust, growth, fragile and sensitive, and then innovates the situational crisis communication theory to build a new hospital crisis classification type. Finally, this paper provides appropriate crisis management strategies for sample hospitals based on the above examples and theories. In addition, the model and classification principles established in this paper can also be applicable to other hospitals, which can provide a theoretical reference for the hospital reputation crisis management level and the adjustment of future management strategies.